Charisma, Grace and Power in Religious Traditions - Lohlker, Rüdiger (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
This Special Issue explores possible theoretical connections and methods to align historical notions and beliefs in mystical grace with sociological theories of charisma, addressing the scholarly challenges that arise from studying charismatic individuals and institutional religious authorities in monotheistic traditions and beyond. Studying the charismatic quality of certain people, locations, and items as a socio-anthropological marker, this project aims for a more nuanced understanding of the history of various religious traditions. Approaching the charisma/grace binary, papers within this Issue analyze the emergence, institutionalization, and growth of religious offices tasked with addressing popular religious needs, and the influence of grace on political power. Emphasis is placed on the connection between charismatic rulers and priestly hierarchies, and the lasting monopoly over grace among charismatic confraternities as a means of social, economic, jurisprudential, and at times political control.